Uso de nanopartículas em modelos animais para tratamento de câncer de próstata: revisão sistemática - Selzler, Michele (2022)
Prostate cancer is the second most common cancer in men's health. Technological innovations are developed in order to improve treatment and reduce the side effects that conventional treatments cause. Therefore, it is necessary to study new treatment approaches for prostate cancer. The aim of the study is to perform a systematic review on the use of nanoparticles in the treatment of prostate cancer in animals. The systematic review was carried out in the PUBMED, SCIELO, LILACS, Cochrane Library and EMBASE databases and the choice of descriptors was based on terms indexed in DECS/MESH, which are: Nanoparticles, Nanomedicine and Prostate Cancer. At the end of the review, six scientific articles were reached, with themes using nanoparticles carrying medications. In all studies, it was possible to observe the benefit of the action of nanoparticles encapsulating drugs in treatments of animals with prostate cancer, different from treatment with free medications that have more adverse effects and decrease the life of the animals studied.